CSS master - Brown, Tiffany B. (SitePoint Pty. Ltd., 2021)
CSS has grown from a language for formatting documents into a robust languagefor designing web applications. Its simplicity is deceptive, however. It belies the complexity of the box model, stacking contexts, specificity, and the cascade. CSS mastery lies in understanding these concepts and how to take advantage of them. This book will show you how to write better, more efficient CSS, and to use the plethora of the new cutting-edge CSS features available to the front-end developer. You'll also learn to master tools that will improve your workflow. Organize your CSS to create efficient, reusable, and maintainable code Discover complex layout techniques: grid layouts, multi-column layouts, and more Use advanced effects: transitions, transforms, filter effect, and animations Re-use and dynamically control CSS values with custom properties Combine CSS and SVG to create seriously powerful graphics This edition has been thoroughly updated to cover newer CSS features and techniques, including new chapters on visual effects and managing document scroll.